Notes on the fecundity of the caridean shrimp Cuapetes americanus (Kingsley, 1878) in two preserved areas in Sao Paulo State: Laje de Santos and Vitoria Island - Rocha de Moraes, Isabela Ribeiro [UNESP]; Ramos Trevisan, Marcia Rafaela [UNESP]; Barros Rodrigues, Gabriel Fellipe [UNESP]; Silva, Alexandre Ribeiro da; Castilho, Antonio Leao [UNESP] (Soc Brasileira Carcinologia, 2022)
In the Atlantic Ocean, the shrimp Cuapetes americanus (Kingsley, 1878) is well distributed. This species has been studied regarding its taxonomic status, distribution records, and some biological and reproductive traits. However, its fecundity and reproductive aspects have never been evaluated in Brazilian waters before. SCUBA (Self Contained Underwater Breathing Apparatus) diving and Artificial Refuge Substrate were used to sample C. americanus specimens quarterly in a sheltered location in the Marine State Parks of Laje de Santos and Vitoria Island for a year (2015-2016). A total of 45 animals (carapace length 1.35-4.54 mm) were sampled: 6 females; 18 ovigerous females; 3 juveniles; and 17 males. The major axis references were employed to analyze the relationship between the second pleura (SPL) and the carapace length (CL). The fecundity was 87.05 +/- 80.50 eggs and it was similar to other populations connected to it, and it was exclusively associated favorably with CL. Despite being a small and inconspicuous species, C. americanus is a caridean shrimp species that has evolved to thrive and breed on continental islands. The importance of the creation and revision of management plans for no-take marine areas on the Brazilian coast is supported when many kinds of information about the ecology and biology of the species are available, such as caridean shrimps, which can be present as a link between trophic levels of the aquatic food web.
Keywords: Crustacean; embryo; no-take areas; Palaemonidae; reproduction